Long-term efficacy of glycopyrrolate on sialorrhea in Goldenhar syndrome: a case report - Gessica Della Bella; Enrico Castelli; Federico Vigevano (BMC, 2022)
Abstract Background Goldenhar syndrome (GS) is a rare congenital disease characterized by impaired development of different facial structures and deformations of the teeth structures. Sialorrhea, which can cause difficulties in breathing and language impairment, is very common in GS and often difficult to treat. This case report highlights the short- and long-term importance of the therapeutic choice - glycopyrronium in oral solution - for the treatment of sialorrhea in children with poly-malformative syndrome, complicated by outcomes of post-hemorrhagic hydrocephalus. Case presentation We report the case of a 6-year-old child with GS, carrying a percutaneous endoscopic gastrostomy after tracheostomy. The child also presented developmental dysfunction of oral motor skills of feeding, complicated by severe sialorrhea, related to the maxillo-facial dysmorphism. Sialorrhea caused several respiratory tract infections and led to an increase in the care burden. Both the inoculations of botulinum toxin and the treatment with scopolamine transdermal patch have shown mild and transient efficacy. The therapeutic choice of glycopyrronium in oral solution was the most suitable for this patient, leading to long-term sialorrhea control. Conclusions This clinical experience represents the first long-term efficacy and tolerability evaluation in using glycopyrrolate oral solution in treating drooling in children with GS. The reduction of drooling over time and the lack of clinically relevant adverse events have contributed to the decrease of respiratory tract infections, the development of oral motor skills, and determining a positive psycho-social impact on the patient's quality of life and her family.